Implementation of the Friday Rohis Program for Muslim Students at SMAN 1 Sangatta Selatan with the Theme Today's Muslim Women: Faith, Health, and Education Towards a Meaningful Life - Nazla Desyulita; Zahrina Farizah Adiliani; Uswatun Hasanah; Fitriah Amina; Eko Nursalim (Al-Mukhlashin: Jurnal Multidisiplin Ilmu, 2025)
Muslimah teenagers play a vital role as the nation’s future generation while also carrying the responsibility of preserving Islamic values in the midst of modern challenges. This study aims to analyze the understanding of Muslimah students at SMAN 1 Sangatta Selatan regarding faith, health, and education, as well as to examine the influence of the Friday Rohis (Islamic Spiritual Program) activities in enhancing their spiritual awareness and religiosity. This research employs a qualitative descriptive approach. Data were collected through participatory observation, interviews with Muslimah students and Islamic teachers, and documentation of activities. Data analysis followed the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. The findings reveal that the Friday Rohis program significantly contributes to shaping students’ understanding of the importance of balancing faith, health, and education. The success of the program is supported by the school’s strong commitment, adequate facilities, and learning approaches that are relevant to teenage life. However, challenges remain in terms of teaching methods and classroom management, which need improvement to create a more conducive learning environment. In conclusion, the Friday Rohis program serves as an empowerment platform for Muslimah students to build a religious, intelligent, and well-characterized identity, enabling them to face the demands of modern times without losing their Islamic values